Comparison of ionization radiation exposure of the nuclear medicine department personnel estimated with different dosimetric methods - Etmańska, Aleksandra; Orlef, Andrzej; Lambrinow, Nikołaj (Contemporary Oncology/Współczesna Onkologia, 2000)
Basically, the absorbed dose measurements for Nuclear Medicine Department personnel are performed with three methods using: film badges, thermoluminescent (TLds) – rings on the fingers, scintillation detector systems for detection of the radiation emitted from the thyroid. These methods were used in order to evaluate radiation exposure of the personnel employed in the Nuclear Medicine Department of the Institute of Oncology, branch Gliwice. The radioactive isotopes used here for diagnostic or therapeutic purposes are 131 I, 99m Tc and 125 I. The typical activities of the isotopes used diagnostically are from the range of 1-20 mCi whereas in case of therapeutical applications activities are of about 150 mCi. In particular about 12 Ci of the 131 I per year is used. Annual doses do not exceed 5% of annual limit as estimated from film badges measurements performed between 1993 and 1999. As estimated by TLDs the limit of 5% is also retained for technicians, the group of the greatest radiation risk. There is a good correlation between the doses measured by both methods. The measurements of the radiation emitted from the thyroid show that the isotope activity measured for patients exceeds detection limit only sporadically and does not go above the Annual Limit Intake of 7%.